2023
DOI: 10.1021/acssuschemeng.3c03248
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Based Covalent Adaptable Network Polymers─When Bio-Based Thermosets Meet Recyclable by Design

Davide Benedetto Tiz,
Filipa A. Vicente,
Ana Kroflič
et al.

Abstract: Covalent adaptable networks (CANs) play an important role in polymer chemistry, as they provide an innovative link between thermoplastics and thermosets. The breakthrough idea behind CANs is to at least partially replace irreversible crosslinks in classic thermoset polymers with dynamic covalent bonds that allow for reversible polymer character and recyclability. Besides, CANs also offer other popular features such as self-healing, weldability, configurability, and shape memory. Most CANs are still petroleum-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 126 publications
(253 reference statements)
0
8
0
Order By: Relevance
“…For example, lignins having a high content of carboxylic acids can be used for the preparation of polymers such as polyesters, and lignin with a high content of hydroxyl groups can be used for the preparation of polymers having covalent adaptable networks to improve the recycling of thermoset materials such as resins. 147,148 It is important to underline that the preparation of such materials is possible thanks to the purity and limited dispersity of the organosolv lignin. Otherwise, the lignin must be purified and fractionated.…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…For example, lignins having a high content of carboxylic acids can be used for the preparation of polymers such as polyesters, and lignin with a high content of hydroxyl groups can be used for the preparation of polymers having covalent adaptable networks to improve the recycling of thermoset materials such as resins. 147,148 It is important to underline that the preparation of such materials is possible thanks to the purity and limited dispersity of the organosolv lignin. Otherwise, the lignin must be purified and fractionated.…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…In the 140 years since the discovery of the Schiff base structures, a large number of related research works have been reported, and in recent years it has become one of the hot research topics due to researchers’ attention to degradable materials. In addition to the aforementioned properties, compounds used for synthesizing Schiff base are gradually being replaced by biobased materials, among which lignin vanillin derivatives are widely used. , …”
Section: Structures Of Degradable or Dynamically Cross-linkable Epoxy...mentioning
confidence: 99%
“…In addition to the aforementioned properties, compounds used for synthesizing Schiff base are gradually being replaced by biobased materials, among which lignin vanillin derivatives are widely used. 117,118 2.4. Disulfide Bonds.…”
Section: Hexahydrotriazine Structuresmentioning
confidence: 99%
“…Also, due to the fast kinetics of the exchange reactions taking place in the network, self-healing behavior and fast stress relaxation has been observed in this class of CANs . In addition, the biobased pool of aldehydes is rather extensive, and includes vanillin, syringaldehyde, , furfural, and functionalized lignin. Imine formation is a well-known reaction in which a primary amine reacts with an aldehyde, yielding a CN moiety, with water as the sole byproduct . Taken together, imine-based CANs represent a promising platform as a substituent for nonrenewable materials since dynamic covalent chemistries allow closed-loop recyclability .…”
Section: Introductionmentioning
confidence: 99%